EFEKTIVITAS PENERAPAN MODEL DIRECT INSTRUCTION DALAM MENINGKATKAN KOMPETENSI DASAR KEILMUAN MAHASISWA PADA PERKULIAHAN FISIKA DASAR II - Zainuddin, Zainuddin (Vidya Karya Jurnal Kependidikan, 2015)
The general purpose of this action research is to describe the effectivity of the direct instruction (DI) model application in increasing the university studentsâ potential scientific basis in Basic Physics 2 under the subject of basic electrostatics. To study the materials and solve the problem of physics in this lecture, the scientific basis competence in the form of procedural skill and declarative knowledge is needed. The research result has shown that the effectivity of the instruction application in increasing the university studentsâ scientific basis competence is 76,4% in the effective category. It is suggested that in the lecture of BasicÂ Physics 2, it is best for the lecturer to apply the direct instruction (DI) model, especially in increasing the university studentsâ scientific basis competence in depicting, presenting, andÂ Â Â explaining the meaning of the basic physical formula of Physics.